Clinical Features and Dynamics of T Cells-Related Markers in Immunocompetent Patients with Cytomegalovirus Hepatitis - Takuya Komura; Takashi Kagaya; Hideo Takayama; Masahiro Yanagi; Takatoshi Yoshio; Saiho Sugimoto; Michiko Nishino; Noriaki Orita; Yoshiro Asahina; Masashi Nishikawa; Shuichi Kaneko; Masashi Unoura (Canadian Journal of Gastroenterology and Hepatology)
Aim. Cytomegalovirus (CMV) can cause hepatitis, encephalomyelitis, and pneumonitis in immunocompromised patients. In contrast, CMV infection of immunocompetent patients can lead to the development of infectious mononucleosis and is typically self-limiting; severe complications are rare. We evaluated the pathophysiology and immunological aspects of CMV hepatitis in recently immunocompetent adult patients. Methods. We examined the clinical features and outcomes of 47 adult immunocompetent patients with CMV hepatitis (29 men, 18 women; mean age, 34 ± 11 years) from January 2005 to August 2019 treated in our hospital. We also assayed T-cell activation to evaluate the immune responses in these patients. Results. Fever (74.5%), hepatosplenomegaly (74.5%), sore throat (36.2%), headache (31.9%), abdominal pain (27.7%), lymphadenopathy (23.4%), and skin rash (6.4%) were present at admission. Complications included gastrointestinal injury (25.5%), neuropathy (4.3%), thrombocytopenia (2.1%), and splenic infarction (2.1%). All patients had a good clinical course without liver failure or transition to chronic liver injury. The time to recover from liver injury ranged from 12 to 142 days (mean, 43.4 ± 28.7 days). The serum sIL-2R level, which reflects T-cell activation, was transiently elevated and correlated with the extent of hepatic inflammation. Conclusions. CMV hepatitis in immunocompetent individuals has a satisfactory outcome, but occasionally results in complications in other organs. The sIL-2R level has potential as a surrogate marker of hepatic inflammation in immunocompetent patients with CMV hepatitis.